Variable selection for individualised treatment rules with discrete outcomes - Bian, Zeyu; Moodie, Erica E M; Shortreed, Susan M; Lambert, Sylvie D; Bhatnagar, Sahir (Journal of the Royal Statistical Society Series C (Applied Statistics), 2024)
Abstract An individualised treatment rule (ITR) is a decision rule that aims to improve individuals’ health outcomes by recommending treatments according to subject-specific information. In observational studies, collected data may contain many variables that are irrelevant to treatment decisions. Including all variables in an ITR could yield low efficiency and a complicated treatment rule that is difficult to implement. Thus, selecting variables to improve the treatment rule is crucial. We propose a doubly robust variable selection method for ITRs, and show that it compares favourably with competing approaches. We illustrate the proposed method on data from an adaptive, web-based stress management tool.